The color of 21st century: Round-table meeting of Filosofska Dumka - Hrabovskyi, Serhii (Filosofska Dumka, 2017)
The legacy of the 20th century — the results of the newest aggressive paganism, combined paradoxically with acquisitions of emancipated intellect which is not constrained with morals — worries to death even in the 19th century. This, in particular, is witnessed by the newest Russian imperialism which has absorbed the mythology of the “coming boor”, traditions of nihilism and anomy, political culture of the Moscow khanate, fed by propagandistic machine of the Kremlin. That is why the leading scientific subjects of the book The Red Century by Myroslav Popovich have gained the acute urgency; the book is a certain encyclopedia of phobias, drawbacks, divergences and latent threats proceeding from that social, political and cultural commonness of the 20th century which resulted in the greatest victims in the history of mankind. The round-table meeting dedicated to this book had the aim to plunge the most urgent narratives of The Red Century in the present notional context. Such a task foresaw the use of interdisciplinary methodological optics with participation of well-known philosophers, philologists, historians with the aim to find the ways of healing from thephobias, drawbacks, and divergences of the century which has passed. The round-table meeting participants discussed the broad range of questions: historical and cultural preconditions of geopolitical events of the 20th century (M. Popovich); lessons that we have to learn proceeding from these events (V. Skurativskyi); content of the present geopolitical situation (S. Proleev); contradictions of modernization and destruction of the moral and political universalism in the context of totalitarianism (A. Yermolenko); doubtful role of ressentiment as the motive force of history (V. Kozlovskyi); problems of identity in formation of the nation-state (O.Bilyi); prospects of the national state system in the 21st century (O. Maiboroda); Ukrainian context of the Second World war (Yu. Shaoval); a phenomenon of stateless subjectness of the Ukrainian nation in the historical context (S. Hrabovskyi).